Renal carcinoma with brain metastases. Prognostic factors and treatment outcomes - A. V. Golanov; A. H. Bekyashev; O. N. Dreval; S. M. Banov; S. R. Ilyalov; E. R. Vetlova; N. A. Antipina; A. A. Durgaryan; A. A. Pogosova (Опухоли головы и шеи)
Introduction. Surgical excision followed by whole-brain radiotherapy (WBRT) is a traditional treatment option for solitary brain metastases (SBM) of renal carcinoma. In the presence of multiple brain metastases of renal carcinoma WBRT remains to be the most common treatment option in this group of patients. However, the effectiveness of WBRT is insufficient due to radioresistance of renal carcinoma. After introduction of the standards in the radiosurgical practice, treatment options of renal carcinoma have been changed, since radiosurgery may overcome WBRT limitations in the treatment of brain metastases of radioresistant tumorsObjective: to study the effectiveness of stereotactic radiosurgery by using “Gamma Knife” device in the treatment of brain metastases of renal carcinoma.Materials and methods. We have analyzed results of the treatment of 112 patients with brain metastases of renal carcinoma who underwent radiosurgical treatment in Moscow Center “Gamma Knife”. Age median of the patients was 58 (33 –77) years. Total number of irradiated metastatic foci – 444, an average number of brain metastases in 1 patient was 4 (1–30). Twenty eight (25.0 %) patients had a single brain metastasis. A median of cumulative volume of brain metastases for each patient was 5.9 (0.1–29.1) cm3. An average value of the marginal dose for metastatic lesion was 22 (12–26) Gy, mean value of isodose used for treatment planning was 64 (39-99) %.Results. An overall survival (OS) rate after radiosurgical treatment was 37.7; 16.4 and 9.3 % for 12, 24 and 36 months, respectively. A median OS was 9.1 months (95% confidence interval (CI) 7.1–11.8). New brain metastases (distant recurrences) following radiosurgical treatment occurred in 44 (54.3 %) patients, with a median of 10.1 months (95 % CI:7-18). Local recurrences after radiosurgical treatment were detected in 19 (17 %) patients with a median time of 6.6 months (95 % CI 4.0–9.6). Factors associated with the best OS: Karnofsky score ≥ 80 (p <0.0369), and the total volume of brain metastases ≤ 5 cm3 (p = 0.0131). Local control was achieved in 96 % of metastatic lesions in 87 % patients. Side effects of radiosurgical treatment occurred in 33.8 % of patients (6% of cases – radionecrosis, 23.8 % – increase in perifocal edema).Conclusion. Radiosurgical treatment alone by using “Gamma Knife” device is an effective treatment option of brain metastases of renal carcinoma, providing a high level of local control of metastatic foci with minimal neurotoxicity. In case of distant recurrence, repeated use of radiosurgery provides a good local control and increase in OS compared with other treatment options.